Single-cell sequencing revealed the recurrence causes of ETV6:RUNX1 fusion-positive B-ALL in children - Guotao Guan; Xiuxiu Wang; Xiuxin Li; Qi Wang; Xiuli Li; Xiaojun Sun; Liying Liu; Yunfeng Lu; Bingju Liu; Xinyu Li; Ping Zhao; Fei Gao; et al. (Molecular and Cellular Probes, 2025)
Objective: The ETV6RUNX1 fusion is the most common genetic abnormality in childhood B-cell acute lymphoblastic leukemia (B-ALL), yet nearly 50 % of relapses occur in patients initially classified as low-risk with this alteration. This study aimed to unravel the underlying pathways driving relapse in ETV6RUNX1 positive B-ALL. Methods: Single-cell RNA sequencing (scRNA-seq) was performed on a cohort of four B-ALL patients with the ETV6RUNX1 fusion (three newly diagnosed and one relapsed case, selected from 25 patients). Results: we discovered that relapsed samples exhibited a decline in T cell populations, an increase in CD8 Tex cells and B cells, and a higher proportion of malignant cells. Gene enrichment analysis demonstrated that IFN-γ response signaling pathways and inflammatory responses were significantly enriched in newly diagnosed samples. Conversely, the relapsed samples showed enrichment in the oxidative phosphorylation and glycolysis pathways. Additionally, analysis of cellular interactions revealed that malignant B cells could interact with T cells through LGALS9-HAVCR2, potentially leading to the exhaustion of effector T cells. Moreover, NPDC1, LEF1, and ERG exhibited higher activity levels in malignant B cells from relapsed patients, highlighting their roles in the progression and maintenance of leukemia. Conclusion: In summary, our study provides valuable insights into the potential causes of relapse in B-ALL patients with ETV6RUNX1, providing a foundation for the identification of prospective therapeutic targets.